Preparing your son for every man's battle : honest conversations about sexual integrity - Arterburn, Stephen, 1953-; Yorkey, Mike.; Stoeker, Fred. (Colorado Springs, CO : Waterbrook Press, 2003)
Publisher description: It$1 (Bs never been easy for a father or mother to talk to a son about sex. For Christian parents, it$1 (Bs always been a challenge to know exactly how to teach God$1 (Bs standards of purity and integrity. But today, the stakes are higher than they$1 (Bve ever been. So it$1 (Bs vital that fathers and mothers prepare their sons to withstand the sexual onslaught of their culture through movies, television, music, and the internet. But what should you say? And when and how should you say it? Now there$1 (Bs help you can trust: Preparing Your Son for Every Man$1 (Bs Battle. The authors behind the best-selling (3z(BEvery Man(3y (Bseries have put together all the resources and guidance you need to experience frank, thorough, and natural conversations with your son about sexual integrity. They offer an effective new communication process that ensures a deep, abiding relationship between you and your son as he moves into his teen years and beyond. Equip your young man with the biblical information and spiritual insights he needs to stand strong, overcome temptation, and experience the blessings of godly obedience$1! =(Bfor the rest of his life.s
The planet "pupiter" -- What does making love mean? -- When girls enter the picture -- What's happening -- Does everyone else know more than I do? -- The ps in the pod -- Flip sides -- My story -- The eyes have it -- Manly eyes -- Self-control -- My story : the sequel -- Sloppy promises -- What's independence? -- We aren't perfect -- Normal or warped? -- Who loves ya? -- The trap -- Treat her like a sister -- Date away -- Are you ready for your number to be called?
Keywords: Sex -- Religious aspects -- Christianity; Teenage boys -- Religious life; Sex instruction for teenagers -- Religious aspects -- Christianity; Child rearing -- Religious aspects -- Christianity